2D 1H and 13C NMR studies of the adducts obtained by cyclostereoselective oligomerization of α, β‒unsaturated arylidenketones promoted by 6 amino‒1, 3‒dimethyl uracil. Issue 4 (2000) - Díaz Díaz, E. E.; Barrios Barrios, H. H.; Gúzman Gúzman, A. A.; Corona Corona, D. D.; Díaz Díaz, R. R.; Fuentes Fuentes, A. A.; Jankowski Jankowski, C. K. C. K.
Abstract : The reaction of the 6‒amino‒1, 3‒dimethyl uracil with the arylidenketones1–4, enabled us to obtain adducts whose structures result from nucleophilic attack and self condensation, yielding with monomeric, dimeric or trimeric derivatives obtained with moderate (40–50%) yields. The reaction was induced by the uracil derivative and the role of this reagent was that of a nucleophile and oligomerization promoter. The structures obtained in this study were mainly elucidated with 1D and 2D high resolution NMR experiments.